SISTEM PEMASARAN DAN KELAYAKAN USAHA AGRIBISNIS PENANGKAR BENIH PADI KELOMPOK TANI WILAYAH KECAMATAN PRAMBANAN - Bharoto, Bharoto (Jurnal Ilmu-Ilmu Pertanian, 2015)
The study was conducted in order to determine how the quality of the seeds produced by farmers seed, knowing how marketing efficiency seed producer of rice seed, and analyse the feasibility of farmers / farmer groups seed, in the Regional District of Prambanan. When the study was conducted in May 2013. Research methods: samples were taken intentionally (purposive) of 30 farmers who dobusiness paddy seed, data were collected by interview using the next questioner descriptive analysis of the data analysed are descriptions that describe and interpret objects in accordance with what it is. Results: Rice seeds produced by farmers good quality has passed the field test and subsequent laboratory testing predicate CERTIFIED SEED. Seed produced basic seed (purple label) results basic seed (white label). Seed producer obtain marketing margin of Rp 3,497, - / kg, marketing efficiency of 77.65%. And the benefits of farmers with land area of 2,078 m2 Rp 3.3434 million * with R / C ratio of 2.52 and 152.10% ROI shows that efforts made rice seed farmer groups Prambanan District worth the effort.